In vivo structural modification of type II arabinogalactans with fungal endo-β-1, 6-galactanase in Arabidopsis - Kikuchi, Aina; Hara, Katsuya; Yoshimi, Yoshihisa; Soga, Kouichi; Takahashi, Daisuke; Kotake, Toshihisa (Frontiers in Plant Science, 2022)
Arabinogalactan-proteins (AGPs) are mysterious extracellular glycoproteins in plants. Although AGPs are highly conserved, their molecular functions remain obscure. The physiological importance of AGPs has been extensively demonstrated with β-Yariv reagent, which specifically binds to AGPs and upon introduction into cells, causes various deleterious effects including growth inhibition and programmed cell death. However, structural features of AGPs that determine their functions have not been identified with β-Yariv reagent. It is known that AGPs are decorated with large type II arabinogalactans (AGs), which are necessary for their functions. Type II AGs consist of a β-1,3-galactan main chain and β-1,6-galactan side chains with auxiliary sugar residues such as L-arabinose and 4-O-methyl-glucuronic acid. While most side chains are short, long side chains such as β-1,6-galactohexaose (β-1,6-Gal6) also exist in type II AGs. To gain insight into the structures important for AGP functions, in vivo structural modification of β-1,6-galactan side chains was performed in Arabidopsis. We generated transgenic Arabidopsis plants expressing a fungal endo-β-1,6-galactanase, Tv6GAL, that degrades long side chains specifically under the control of dexamethasone (Dex). Two of 6 transgenic lines obtained showed more than 40 times activity of endo-β-1,6-galactanase when treated with Dex. Structural analysis indicated that long side chains such as β-1,6-Gal5 and β-1,6-Gal6 were significantly reduced compared to wild-type plants. Tv6GAL induction caused retarded growth of seedlings, which had a reduced amount of cellulose in cell walls. These results suggest that long β-1,6-galactan side chains are necessary for normal cellulose synthesis and/or deposition as their defect affects cell growth in plants.